Pentingnya Kesehatan Mantal Bagi Guru di Masa Pandemi - Fitriyanti Sulaiman; Muhammad Junaedi Mahyuddin; M Yunus Sudirman; Irmayanti Pratiwi; Masnawati Masse (LP2M Universitas Muhammadiyah Enrekang, 2022)
The Covid-19 pandemic has forced many people from all age groups in various countries to adapt to new norms/habits that can interfere with individual mental health. The impact of Covid-19 that hit Indonesia made teachers and students feel anxious, many people lost their jobs due to the declining economy, and had to be confined to their rooms during the lockdown, all of which were threatened with a decline in mental health. This community service project aims to educate the general public, especially teachers, about the importance of maintaining mental health, both during and after the epidemic (next life). Through mental health seminars, the success of the program is evaluated using a survey methodology and a mental health questionnaire. It can be concluded that the teacher's ability to overcome mental health problems is influenced by the availability of information and knowledge about mental health.